2018
DOI: 10.3389/fimmu.2018.01832
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate and Dietary Soluble Fiber Improve Neuroinflammation Associated With Aging in Mice

Abstract: Aging results in chronic systemic inflammation that can alter neuroinflammation of the brain. Specifically, microglia shift to a pro-inflammatory phenotype predisposing them to hyperactivation upon stimulation by peripheral immune signals. It is proposed that certain nutrients can delay brain aging by preventing or reversing microglial hyperactivation. Butyrate, a short-chain fatty acid (SCFA) produced primarily by bacterial fermentation of fiber in the colon, has been extensively studied pharmacologically as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(170 citation statements)
references
References 62 publications
6
162
0
2
Order By: Relevance
“…A study of monozygotic twins has revealed significant differences in overall content and genomic distribution of 5-methylcytosine DNA and histone acetylation in older but not in younger twins [14]. A similar result has also been obtained from a longitudinal study in older Swedish monozygotic and dizygotic twins [15], indicative of the environmental effects on epigenetic alterations with age [16]. …”
Section: Epigenetic Mechanisms and Their Relevance To Agingmentioning
confidence: 58%
“…A study of monozygotic twins has revealed significant differences in overall content and genomic distribution of 5-methylcytosine DNA and histone acetylation in older but not in younger twins [14]. A similar result has also been obtained from a longitudinal study in older Swedish monozygotic and dizygotic twins [15], indicative of the environmental effects on epigenetic alterations with age [16]. …”
Section: Epigenetic Mechanisms and Their Relevance To Agingmentioning
confidence: 58%
“…Most dietary fibers, including inulin, are not digested in the small intestine, but are metabolized by the microbiota in the large intestine (Macfarlane & Macfarlane, 2012). The major SCFA products of microbial fermentation of fibers in the gut are acetic, propionic and butyric acids (Cummings et al, 1987;Matt et al, 2018). Through specific receptors, SCFAs play important roles in the maintenance of health, energy metabolism and the prevention of certain diseases (Alexander et al, 2019;Kimura et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate also has anti-inflammatory properties; for instance, butyrate inhibited proinflammatory activities of IECs in vitro (Elce et al, 2017) and interacted with IECs to regulate host T cell responses (Lew et al, 2018;Xu et al, 2018). Butyrate may also diffuse into the systemic circulation to exert anti-inflammatory effects on various organs and tissues, including the brain (McNabney and Henagan, 2017;Matt et al, 2018). Indeed, butyrate has been shown to normalize behavior of depressed rodents through epigenetic regulations of hippocampal BDNF expression (Han et al, 2014;Wei et al, 2014;Sun et al, 2016).…”
Section: Butyrate Intestinal Barrier and Bdnf Expressionmentioning
confidence: 99%